Characterisation and pathogenicity of Marasmiellus spp. isolated from oil palm and coconut in West Malaysia - Abdulsada, Bushra Subair (2012)
Species of Marasmiellus are of widespread occurrence causing numerous diseases on a wide range of tropical crops. Although Marasmiellus palmivorus has been reported from only a few countries, its records of growth behaviour and habitat suggest the existence of this fungus in countries where oil palm and coconut are cultivated commercially. There is lack of information on the characterization and pathogenicity of species in Malaysia and globally. In addition, the pathogenicity of M. palmivorus has never been proven. The aim of this study was to isolate the fungus from diseased oil palm and coconut, identify and characterize the causal pathogen of bunch rot of oil palm and embryo and shoot rot of germinating coconuts in West Malaysia using morphological and molecular characteristics. The pathogenicity tests and cross inoculations of isolates on oil palm (fruits, seeds, and seedlings) and coconut seeds in the glasshouse were also conducted. Pure cultures of Marasmiellus were isolated from samples of diseased oil palm fruits, coconut seeds, basidiocarps and rhizomorphs. Identification of fungus was done based on characteristics observed from cultural and molecular methods. Pathogenicity tests were conducted to confirm pathogenicity of oil palm and coconut isolates in the glasshouse. Samples were collected from six locations in two states in West Malaysia from which 25 isolates were obtained for study. Pure cultures of isolates produced colonies that were fast growing on Potato Dextrose Agar (PDA) and Malt Extract Agar (MEA) media, with dense white mycelia and lighter orange colour at the center, binucleate hyphae, were mostly not immersed in agar. Clamp connections were abundantly present in all isolates. The optimum temperature for all isolates growth was 30°C, and all were capable of growing on a wide range of pH. Morphology of basidiocarps and basidiospores was found to be similar with differences in the size and colour of basidiocarps and size of basidiospores. The fungus pileus colour was pale orange in the middle, with a depressed center, and measured 9-30mm in diameter. The stipe was white, pale orange, silky, base was initially filled with tissues then becoming hollow, bulbous and eccentric and measured 7-29mm in diameter. The basidiospores were hyaline, oblong to ellipsoid and smooth. Molecular characterization of isolates based on nLSU region and BLAST results indicated that all 25 isolates sequences were 99% identical to that of Marasmiellus palmivorus AY639434 from USA–Hawaii. Phylogenetic analysis of 25 isolates based on neighbor joining method on nLSU region grouped them in the same cluster with M. palmivorus AY639434 from USA–Hawaii and distinct from other genera in Marasmiaceae family. Phylogenetic analysis based on neighbor joining method on ITS regions similarly grouped them in the same cluster. There was no previous sequence deposited in GeneBank for M. palmivorus and this is the first sequence for this region. Ten different isolates of Marasmiellus palmivorus successfully produced high numbers of basidiocarps in the glasshouse when cultured using two artificial methods: whole wheat grain and rubber wood block. Pathogenicity tests on oil palm fruits showed the highest disease severity caused by isolates C3, C4, and C5 with no significant difference between wounded and unwounded fruits. All isolates tested infected shoots and radicles emerging from seed recognizable as two types of dampingoff: pre-emergence and post-emergence, decay of hypocotyl near the soil lines and root tissues. The pre and post-emergence damping off ranged from 37.5 to 100 %. Pathogenicity tests on oil palm seedlings showed significant differences in disease incidence between isolates. Five isolates (C3, C4, C5, Bangi1, and MPOB1) were pathogenic to coconut seeds. Isolates C3, C4 and C5 caused highest percentage disease incidence on coconut seeds. Post-emergence disease of roots of coconut seedlings was considered a new finding. Histopathological examinations of the root tissues of oil palm and coconut showed the presence of fungal hyphae within pith, xylem, cortex and epidermis cells with brownish inclusions found in the phloem and pith. The results obtained from pathogenicity tests confirmed M. palmivorus to be potentially pathogenic to oil palm and coconut and causing various disorders.